Re-Envisioning Community Gardens: Exploring the value of community gardens in supporting young people’s development through informal education (Concept: The Journal of Contemporary Community Education Practice Theory, 2024)
After feeling the impact of the Covid-19 pandemic, access to outdoor spaces as sites for learning, growth, and connection has grown in importance for young people’s learning through play, creativity, and risk-taking. In addition, government cuts to youth and community work alongside restrictions within formal education, demonstrates a greater need to protect and re-envision how we view spaces like community gardens as valuable learning grounds for young people to access outside schools. This article aims to demonstrate the importance of learning in the outdoor environment of community gardens. Drawing on data from both Youth Workers and young people, it will advocate for the significance of community gardens for the growth and progression of young people through positive education development using informal learning techniques. It concludes that informal education is vital for young people's educational growth and development, particularly in outdoor settings like community gardens focusing on hands-on experiences and learning through play and the senses. After advocating for the importance of community gardens, it outlines how funding for youth and community sectors like community gardens could be increased and prioritised to maintain active sites outside of schools.